2000
DOI: 10.1002/(sici)1099-1085(20000228)14:3<369::aid-hyp943>3.3.co;2-g
|View full text |Cite
|
Sign up to set email alerts
|

Stormflow generation in steep forested headwaters: a linked hydrogeomorphic paradigm

Abstract: Abstract:Headwater catchments are sources of sediments, nutrients, and biota for larger streams, yet the hydrologic pathways that transport these materials remain unclear. Dynamics of storm¯ow generation related to landform attributes and antecedent rainfall were investigated in a steep forested headwater catchment at Hitachi Ohta Experimental Watershed, Japan. Such headwater catchments are deeply incised: the narrow riparian corridors have limited capacities to store and transmit water to streams. Storm runo … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
196
2

Year Published

2012
2012
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(212 citation statements)
references
References 0 publications
14
196
2
Order By: Relevance
“…This indicates that the soil moisture measured at and near the base of a valley appears more important than the soil moisture conditions at the upper and the middle hillslope. This is consistent with results published by Sidle et al (2000), McGlynn and McDonnell (2003), McGlynn and Seibert (2003) and Klaus et al (2015), who also emphasize the importance of the riparian zone for the runoff response of a catchment. Woods et al (1997) additionally indicate the relevance of riparian zones in the forefront of convergent hillslopes.…”
Section: Detecting the Optimal Placement Of Soil Moisture Sensorssupporting
confidence: 92%
“…This indicates that the soil moisture measured at and near the base of a valley appears more important than the soil moisture conditions at the upper and the middle hillslope. This is consistent with results published by Sidle et al (2000), McGlynn and McDonnell (2003), McGlynn and Seibert (2003) and Klaus et al (2015), who also emphasize the importance of the riparian zone for the runoff response of a catchment. Woods et al (1997) additionally indicate the relevance of riparian zones in the forefront of convergent hillslopes.…”
Section: Detecting the Optimal Placement Of Soil Moisture Sensorssupporting
confidence: 92%
“…sustain baseflow (Tetzlaff and Soulsby, 2008). Other studies showed that during baseflow conditions the riparian zone acts as the main input to streamflow generation (Penna et al, 2014;Sidle et al, 2000). Our studied headwaters were lacking such a valley aquifer and riparian zone.…”
Section: Wider Implications On Pre-alpine Baseflowmentioning
confidence: 76%
“…The wetlands are prominent landscape units with large storage capacity and areal extent (30-60% of the subcatchment area) but during baseflow these features mostly act as passive units not significantly contributing to baseflow. Consequently, pre-alpine headwaters with similar climate, geology and topography are, during baseflow, not just the sum of different landscape units, but are rather dominated by the arrangement of connected (active) or disconnected (passive) landscape units as conceptualised by Sidle et al (2000) and Ambroise (2004).…”
Section: Wider Implications On Pre-alpine Baseflowmentioning
confidence: 99%
See 1 more Smart Citation
“…It is not clear whether this intermittency correspond to the natural flow regime of the study streams or it is caused by land use changes because there are not historical flow records for the study area. Hydrological variability among headwater catchments can be high due to spatial variation in geology, soil depth, topography, and vegetation, and this variation decreases as drainage area reaches 1 km 2 (Woods et al, 1995;Siddle et al, 2000;Gomi et al, 2002;Bruijnzeel, 2004), which is greater than the area of half of our study catchments (Table I). This natural variation among small catchments could explain, in part, differences in flow regime among the study streams.…”
Section: Discussionmentioning
confidence: 87%